BOOK REVIEW Sinsoekers: Tussen twyfel en troos - M. Laubscher (Acta Theologica)
A book review of "Sinsoekers: Tussen twyfel en troos" by Cilliers, J. (Aucklandpark: UJ Pers, 2023), pp. 203, ISBN: 978-1-7764827-6-4. The review is in Afrikaans.